2009
DOI: 10.1002/lt.21999
|View full text |Cite
|
Sign up to set email alerts
|

Report of a national conference on liver allocation in patients with hepatocellular carcinoma in the United States

Abstract: A national conference was held to better characterize the long-term outcomes of liver transplantation (LT) for patients with hepatocellular carcinoma (HCC) and to assess whether it is justified to continue the policy of assigning increased priority for candidates with early-stage HCC on the transplant waiting list in the United States. The objectives of the conference were to address specific HCC issues as they relate to liver allocation, develop a standardized pathology report form for the assessment of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
367
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 375 publications
(385 citation statements)
references
References 51 publications
14
367
1
3
Order By: Relevance
“…17,25,89,109,110 Nevertheless, the risk of dropout due to cancer progression in patients meeting the MC at the time of listing still exists and is as high as 30% if no treatment is pursued; however, bridging therapies during the waiting period (either ablation or locoregional approaches) are able to reduce the dropout rate into the range of 0% to 21%. 111,112 In general, the dropout risk increases as the waiting time progresses; in the case of HCC patients who are listed for more than 3 months, the dropout rate is greater than that observed for patients with nonmalignant diseases. 112 Although there is no proven posttransplant advantage in treating patients within the MC who are listed for transplantation, the available evidence (average NOS score ÂĽ 7) 17,22,23,35,80 indicates that listed patients within the MC who are treated while they are on the waiting list with ablation (preferred for single nodules < 3 cm) or transarterial chemoembolization (TACE; preferred for HCCs > 3 cm or with a multinodular pattern) have reduced dropout rates in comparison with historical untreated controls.…”
Section: Should Patients Within the MC Be Treated While They Are On Tmentioning
confidence: 99%
See 1 more Smart Citation
“…17,25,89,109,110 Nevertheless, the risk of dropout due to cancer progression in patients meeting the MC at the time of listing still exists and is as high as 30% if no treatment is pursued; however, bridging therapies during the waiting period (either ablation or locoregional approaches) are able to reduce the dropout rate into the range of 0% to 21%. 111,112 In general, the dropout risk increases as the waiting time progresses; in the case of HCC patients who are listed for more than 3 months, the dropout rate is greater than that observed for patients with nonmalignant diseases. 112 Although there is no proven posttransplant advantage in treating patients within the MC who are listed for transplantation, the available evidence (average NOS score ÂĽ 7) 17,22,23,35,80 indicates that listed patients within the MC who are treated while they are on the waiting list with ablation (preferred for single nodules < 3 cm) or transarterial chemoembolization (TACE; preferred for HCCs > 3 cm or with a multinodular pattern) have reduced dropout rates in comparison with historical untreated controls.…”
Section: Should Patients Within the MC Be Treated While They Are On Tmentioning
confidence: 99%
“…Although precise data for the subset of patients meeting the MC are not available, evidence shows that pretransplant treatments are widely used, regardless of the tumor stage, to prevent dropout from the list and possibly to improve post-LT survival. 111 In a recent study using a Markov model simulation and restrictive assumptions, sorafenib was shown to be cost-effective in comparison with no therapy for patients within the MC (ie, United Network for Organ Sharing stage T2) who were waiting for transplantation, particularly when the median time to transplantation was <6 months. 113 Molecular-targeted therapies during the LT waiting period for patients with HCC are likely to be tested in the near future.…”
Section: Should Patients Within the MC Be Treated While They Are On Tmentioning
confidence: 99%
“…Although data supporting an extension of the selection criteria are limited, an apparent opportunity for extending these criteria has arisen. 27 However, because of the shortage of donor organs, hepatologists are obliged to maintain strict selection criteria for liver transplantation. In particular, patients with HCC who do not meet the Milan criteria have limited access to liver transplantation, and alternative therapeutic approaches for these patients should be considered.…”
Section: Should Liver Transplantation Be Restricted To a Subgroup Of mentioning
confidence: 99%
“…44 Changes in the allocation of points have been proposed, and a 3-month waiting time for the detection of patients with rapidly progressing tumors may be adopted so that patients with aggressive tumors are not accepted for liver transplantation. 27,40 Despite the application of MELD exceptions, the survival rate of patients with HCC after liver transplantation is still not as good as the survival rate of patients without HCC who have similar MELD scores. 40 The development of equitable policies has been hampered by a lack of robust predictors for identifying patients at a high risk of disease progression and patients at a high risk of dropout.…”
Section: Prioritizing Equitable Policies For Liver Transplantation Inmentioning
confidence: 99%
“…The authors concluded that the MELD allocation system would not be helpful in New Zealand, which has a single transplant center and organ procurement organization, and I am in agreement with this. Their results are not surprising in light of the fact that median waiting time prior to transplantation was 72 days and the MELD Patients were listed for HCC if they met University of California, San Francisco (UCSF) criteria [22] or Milan criteria [23] and were assigned 24 points instead of 22. There was no real delta MELD, not unexpected since the waiting time was short.…”
mentioning
confidence: 99%